Philippine fisheries trade with ASEAN chokepoints to AEC 2015 - Israel, Danilo C. (2013)
The planned establishment of an ASEAN Economic Community (AEC) in 2015 has induced member-countries to implement concrete measures to improve their readiness for it. The Philippine fisheries sector has undertaken some steps to enhance its competitiveness leading to the new ASEAN arrangement. Nevertheless, critical chokepoints in its supply chain remain, raising questions on its ability to adequately meet the AEC challenges.

This Policy Note provides a brief background of the sector, reviews Philippine fisheries trade with the ASEAN, summarizes the critical chokepoints in the fisheries supply chain, and recommends measures for improvement. While fish trade between the Philippines and other ASEAN countries is low at present, there is hope that if and when the AEC materializes, the situation could significantly improve. Effectively addressing the different chokepoints will help promote the chance of success.
Keywords: Fishery economics